Effects of Smoking Opportunity on Cue-Elicited Urge: A Facial Coding Analysis - Sayette, Michael A. (2003)
The authors analyzed smokers’ facial expressions using the Facial Action Coding System (P. Ekman & W. V. Friesen, 1978) under varying smoking opportunity conditions. In Experiment 1, smokers first were told that they either could (told-yes) or could not (told-no) smoke during the study. Told-yes smokers reported higher urges than did told-no smokers. Unexpectedly, told-yes smokers became increasingly likely to manifest expressions related to negative affect and less likely to evince expressions related to positive affect, compared with told-no smokers. In Experiment 2, smokers were more likely to show positive affect-related expressions if the delay was 15 s than if it was 60 s. Craving may be related to both a desire to use and an impatient desire to use immediately.